Spn1, Spt4, Spt5, and Spt6 preserve chromatin structure over promoters and open reading frames - Tonsager, Andrew Jordan, author; Stargell, Laurie A., advisor; Hansen, Jeffrey C., committee member; Santangelo, Thomas, committee member; Argueso, Juan Lucas, committee member (Colorado State University. Libraries, 2024)
The eukaryotic chromatin landscape presents formidable nucleosomal barriers for processes that require access to DNA, such as transcription. These barriers are overcome through the action of many factors, including histone chaperones Spn1, Spt5, Spt6, and FACT and transcription elongation factor Spt4. However, it is poorly understood how each contributes to this process. To ascertain the role that these factors play on preserving chromatin structure over the genome, this thesis has utilized micrococcal nuclease digestion followed by sequencing (MNase-seq) to analyze chromatin protections in the yeast genome in cells expressing numerous mutant alleles of these factors. Extensive characterization of MNase-protected fragments in a wide range of sizes established that the essential histone chaperone Spn1 preserves both nucleosomal and subnucleosomal structures over both promoters and open reading frames across the genome. Additional analyses from existing MNase-seq datasets demonstrated the extent to which Spn1 and other RNAPII-associated factors maintain nucleosome features over genes of varied characteristics. The study of factors described in this thesis is performed in living cells, which have been genetically modified to express mutant alleles of chromatin factors. This thesis also describes a course-based undergraduate research experience (CURE) developed to introduce upper-level biochemistry students to techniques in yeast genome engineering in an authentic research setting.
Keywords: course-based undergraduate research experience; yeast; Spn1; chromatin